2008
DOI: 10.1002/14651858.cd006438.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Open surgical procedures for incisional hernias

Abstract: There is good evidence from three trials that open mesh repair is superior to suture repair in terms of recurrences, but inferior when considering wound infection. Six trials yielded insufficient evidence as to which type of mesh or which mesh position (on- or sublay) should be used. There was also insufficient evidence to advocate the use of the components separation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
174
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(180 citation statements)
references
References 23 publications
3
174
0
3
Order By: Relevance
“…In a randomized controlled trial with a 5-year follow-up, Weber et al (21) reported that sublay mesh repair has a significantly higher recurrence rate than onlay mesh repair (20% vs. 12%, respectively). Den Hartog et al (20) reported recurrence rates of 7.4% by onlay mesh repair and 13.6% by sublay mesh repair. Moreover, Venclauskas et al (18) reported recurrence rates of 10.5% using onlay mesh repair and 2% using sublay mesh repair.…”
Section: Incisional Hernia Remains a Major Problem After Laparotomymentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled trial with a 5-year follow-up, Weber et al (21) reported that sublay mesh repair has a significantly higher recurrence rate than onlay mesh repair (20% vs. 12%, respectively). Den Hartog et al (20) reported recurrence rates of 7.4% by onlay mesh repair and 13.6% by sublay mesh repair. Moreover, Venclauskas et al (18) reported recurrence rates of 10.5% using onlay mesh repair and 2% using sublay mesh repair.…”
Section: Incisional Hernia Remains a Major Problem After Laparotomymentioning
confidence: 99%
“…Considering onlay and sublay mesh repair techniques, Venclauskas et al (18) reported similar postoperative pain scores both at rest and during physical activity. However, Den Hartog et al (20) reported sublay mesh repair to cause less pain than onlay mesh repair. Similarly, our results show that the sublay group had lower VAS scores at the second and 24 th hours.…”
Section: Incisional Hernia Remains a Major Problem After Laparotomymentioning
confidence: 99%
“…At present synthetic meshes are most often categorized as macroporous, microporous, or composite [7]. Macroporous meshes include polypropylene-monofilament and polyestermultifilament meshes, among many others [8].…”
Section: Introductionmentioning
confidence: 99%
“…[13] Although surgical techniques have improved, recurrence is still a common complication of surgically repaired abdominal walls, and is more frequent in open suture repairs than in tension-free repairs, with recurrence rates of 54% and 32%, respectively. [14][15][16][17] Given that mesh implantation appears to be the best option for abdominal wall repair, the technique has peaked the interest of the medical community, and the general research focus has shifted towards analyzing the compatibility of different materials for mesh production.…”
Section: Discussionmentioning
confidence: 99%